Answer:
Let's solve for f.
fx=
4x−3
x−10
Step 1: Multiply both sides by x-10.
fx2−10fx=4x−3
Step 2: Factor out variable f.
f(x2−10x)=4x−3
Step 3: Divide both sides by x^2-10x.
f(x2−10x)
x2−10x
=
4x−3
x2−10x
f=
4x−3
x2−10x
Answer:
f=
4x−3
x2−10x
Let's solve for g.
gx=
2x−8
x−10
Step 1: Multiply both sides by x-10.
gx2−10gx=2x−8
Step 2: Factor out variable g.
g(x2−10x)=2x−8
Step 3: Divide both sides by x^2-10x.
g(x2−10x)
x2−10x
=
2x−8
x2−10x
g=
2x−8
x2−10x
Answer:
g=
2x−8
x2−10x
Step-by-step explanation:
(-4,-3) hola! My friend and thanks for asking mama Sita.
I think you meant half when you said of right... if u did the answer is <span>2/25 divided by 1/2 wich is .04</span>
Answer:
Jenny's percentage isn't correct
Step-by-step explanation:
You'd have to divide first:
38 / 32 = 1.1875 = (rounded) 1.19%
The percentage increase is 1.19%
Answer:
i think the answer is x=1